â€œBELENGGU BENALUâ€: KOMPOSISI KOLABORASI-INTERPRETATIF MENGENAI PENGARUH AKULTURASI BUDAYA BARAT PADA MUSIK BATAK TOBA â€œUNING-UNINGANâ€ - Matanari, Oang Gabriel; Darmayuda, I Komang; Ardini, Ni Wayan (Institut Seni Indonesia Denpasar, 2019)
Foreign culture that enters Batak land in North Sumatera, Indonesia, has a great influence on the development of the Batak Toba music or Uning-uningan (an ensemble transformed between Gondang Hasapi consisting of Sarune Etek, Hasapi Doal, Hasapi Ende, Garantung, as well as Hesek and Gondang Sabangunan/Bolon (Taganing, Ogung (Gong), Odap, Hesek and Sarune Bolon). Nowadays, most of the traditional Batak Toba ceremonials present the concept of Uning-uningan music with keyboard accompaniment, especially in the situations that there is a budget limitation which gives a large space for single organ players (keyboardist) to apply Uning-uningan musical repertoires only with an instrument (i.e. the keyboard). This certainly gives negative influence on the existence of the Batak Toba traditional music. As a result the influence that happened because of the western culture makes the people of Batak Toba prefers the musical concept of Uning-uningan with keyboard accompaniment. Therefore, the concern of the author and composer in responding to the influence of acculturation on the existence of Batak Toba traditional music is outlined in musical composition entitled ?Belenggu Benalu?. Through this music composition hopefully the people of Batak Toba, especially Batak musicians are aware and participate in preserving and maintaining Uning-uningan and other traditional Batak music as one of the identities of the Indonesian art and culture diversity.